Sharia Governance of Islamic Mutual Funds in Indonesia: Reconstructing DSN-MUI Fatwa Number 20/2001 - Nurul Mu’minaati; Idris (Jurnal Smart Hukum (JSH), 2027)
The development of Islamic mutual funds in Indonesia highlights the growing importance of integrating Sharia principles, capital market regulation, and modern investment governance. DSN-MUI Fatwa Number 20/DSN-MUI/IV/2001 on Guidelines for Investment in Islamic Mutual Funds constitutes one of the primary normative foundations for their operations in Indonesia. However, regulatory developments, the digitalization of investment services, the rising number of retail investors, and the increasing complexity of financial instruments have created new challenges in implementing the fatwa particularly regarding contractual arrangements, Sharia screening, cleansing mechanisms, information disclosure, and the effectiveness of Sharia Supervisory Board (SSB) oversight. This study analyzes the implementation of DSN-MUI Fatwa Number 20/DSN-MUI/IV/2001 in the management of Islamic mutual funds in Indonesia from the perspective of Islamic economic law and formulates an appropriate direction for reconstructing its implementation. It employs normative legal research using statutory, conceptual, and regulatory approaches, supported by an analysis of developments in Islamic mutual fund management practices. Legal materials are examined qualitatively and prescriptively by tracing the relationship between the fatwa, Islamic capital market regulations, Islamic economic law principles, and the governance demands of contemporary investment activities. The findings show that, normatively, implementation of the fatwa has been strengthened through Islamic capital market regulations and Sharia supervisory mechanisms. Nevertheless, its application remains largely oriented toward formal compliance and requires stronger emphasis on substantive Sharia compliance, risk-based supervision, digital transparency, and interinstitutional coordination. This study proposes an Adaptive Sharia Governance Model (ASGM) built on four pillars: Substantive Sharia Compliance, Risk-Based Sharia Supervision, Digital Sharia Governance, and Collaborative Regulatory Framework. The model is designed to ensure that implementation of the fatwa can adapt to technological change and industry complexity without compromising Sharia substance, while strengthening investor protection, transparency, accountability, and public interest (maṣlaḥah) in Islamic mutual fund management.